Development of trade relations of Bosnia and Hercegovina with Slovenia: Different aspects and characteristics - Snježana Brkić (Naše gospodarstvo / Our Economy, 2019)
The paper is aimed at identifying characteristics of trade relations of Bosnia and Herzegovina (BiH) with the Republic of Slovenia (Slovenia) in order to contribute to determining the position of BiH in its bilateral trade. The foreign trade analysis has been performed in the context of the changing trade regime between the two countries, thereby including both institutional and functional aspects of bilateral trade relations development. Different trade indicators have been calculated and interpreted for the period of 2003-2017 and/or for selected years which were identified by a change in the institutional regulations of mutual trade flows. The research results indicate increasing trade intensity between the two countries, with almost balanced export and import flows and with prevailing inter-industry trade. The trade performance of BiH has significantly improved, with increasing intra-industry specialization and trade. However, the export structure and comparative advantage pattern are not favourable toward BiH, which points to the need for improving the country's position in its trade with Slovenia.
Keywords: F10; F13; F14; 330; trade relations; trade regime; bilateral trade analysis; Bosnia and Herzegovina (BiH); the Republic of Slovenia (Slovenia)